Phenotypes, Functions, and Clinical Relevance of Regulatory B Cells in Cancer - Shang, Jin; Zha, Haoran; Sun, Yufa (Frontiers in Immunology, 2020)
In immune system, B cells are classically positive modulators that regulate inflammation and immune responses. Regulatory B cells (Bregs) are a subset of B cells which play crucial roles in various conditions, including infection, allergies, autoimmune diseases, transplantation, and tumors. Until now, unequivocal surface markers for Bregs still lack consensus, although numerous Breg subsets have been identified. Generally, Bregs exert their immunoregulatory functions mainly through cytokine secretion and intercellular contact. In the tumor microenvironment, Bregs suppress effector T cells, induce regulatory T cells and target other tumor-infiltrating immune cells, such as myeloid-derived suppressor cells, natural killer cells and macrophages, to hamper anti-tumor immunity. Meanwhile, the cross-regulations between Bregs and tumor cells often result in tumor escape from immunosurveillance. In addition, accumulating evidence suggests that Bregs are closely associated with many clinicopathological factors of cancer patients and might be potential biomarkers for accessing patient survival. Thus, Bregs are potential therapeutic targets for future immunotherapy in cancer patients. In this review, we will discuss the phenotypes, functions, and clinical relevance of Bregs in cancer.